A Meta-Analysis of the Effect of Multisession Transcranial Direct Current Stimulation on Cognition in Dementia and Mild Cognitive Impairment. (July 2019) - Inagawa, Takuma; Narita, Zui; Sugawara, Norio; Maruo, Kazushi; Stickley, Andrew; Yokoi, Yuma; Sumiyoshi, Tomiki
There have been increasing efforts to investigate the effects of neuromodulation techniques, such as transcranial direct current stimulation (tDCS), on cognitive impairment in dementia and related conditions. In this systematic review and meta-analysis, we assessed the efficacy of multisession anodal tDCS compared with sham stimulation for improving global cognition and specific cognitive domains in both Alzheimer's disease and mild cognitive impairment. Eight articles meeting the criteria for inclusion in the meta-analysis were selected. Five studies used the Mini-Mental State Examination to examine mild cognitive impairment and dementia. In a fixed-effect model, there was a mean difference in the change score of −0.13 points. Three trials for dementia using the Alzheimer's Disease Assessment Scale–Cognition showed a mean difference of −0.53 points. At present, there is a lack of clear evidence concerning the efficacy of multisession anodal tDCS due to the small number of studies and different measures used. This underscores the need for further investigations using larger samples and common outcome measures.